Bringing Light to the Darkness: COVID-19 and Survivance of American Indians and Alaska Natives (Mary Ann Liebert, 2021)
The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) sweeping across our country has reawakened the fear, pain, stigma, and loss of past outbreaks of infectious diseases among American Indians and Alaska Natives. Attention to the pandemic has emphasized the challenges it poses for Native peoples: their vulnerability, the heartbreaking battle to constrain contagion, the lack of resources to care for those afflicted by the virus, and the mounting consequences for individuals, families, and community. We highlight the factors that contribute to them but conclude by underscoring the intrinsic strengths and resilience, which, in combination with modern public health tools, promise to resolve them.